2023
DOI: 10.3390/jcm12020697
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infections May Be Associated with Henoch–Schönlein Purpura

Abstract: Henoch–Schönlein purpura or IgA vasculitis is the most common type of pediatric vasculitis that may affect adults as well. It is classified as a type of small-vessel vasculitis. It can cause cutaneous and systemic symptoms with a minority of patients developing kidney failure. Little is known about the specific pathophysiology of this disorder, except that it is believed to occur in individuals with abnormally glycosylated IgA1. Serum aberrant IgA1 may form large antigen–antibody complexes which, due to a defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 72 publications
(83 reference statements)
0
17
1
Order By: Relevance
“…Viral infections have been considered as a possible trigger of HSP, with a long list of candidate viral agents proposed in the literature. 2,3,20,24 Although we considered 10 of these agents in our study, we found that only hRV-hEV was associated with HSP, with a calculated attributable fraction of 17.1%. Unfortunately, our data did not allow us to further separate hEV from hRV, as the RT-PCR primers of the virus detection kits used in French hospitals detect both rhinoviruses and enteroviruses.…”
Section: Jama Network Open | Rheumatologymentioning
confidence: 86%
See 2 more Smart Citations
“…Viral infections have been considered as a possible trigger of HSP, with a long list of candidate viral agents proposed in the literature. 2,3,20,24 Although we considered 10 of these agents in our study, we found that only hRV-hEV was associated with HSP, with a calculated attributable fraction of 17.1%. Unfortunately, our data did not allow us to further separate hEV from hRV, as the RT-PCR primers of the virus detection kits used in French hospitals detect both rhinoviruses and enteroviruses.…”
Section: Jama Network Open | Rheumatologymentioning
confidence: 86%
“…Henoch-Schönlein purpura (HSP), also known as immunoglobulin A (IgA) vasculitis in adults, is the most common type of vasculitis in children, affecting mainly small blood vessels and caused by the deposition of immune complexes . It typically affects the skin and less frequently the digestive system, joints, and kidneys . The exact cause and underlying mechanisms of HSP are not fully understood, but it is believed to result from an abnormal inflammatory response triggered by antigenic stimuli, particularly infectious agents, in individuals with a genetic predisposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case report, a reason for reflection is also the diagnosis of TA one month after the SARS-CoV-2 infection considering the already-known relationship between viral infections and autoimmune disease [ 13 ]. Respiratory tract viruses, including parainfluenza virus (PIV), influenza, respiratory syncytial virus (RSV), and adenovirus, are commonly associated with Henoch–Schönlein Purpura or IgA vasculitis, a type of small vessel vasculitis [ 14 ]. Hepatitis C virus (HCV) is the most frequent cause of cryoglobulinemic vasculitis, a vasculitis of small and medium vessels due to the deposition of mixed cryoglobulins and immunocomplexes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although HSP is usually triggered by an antigenic stimulus including infectious agents, drugs, vaccines, cold, an insect bite or foods, it is rarely triggered by VZV infection in children. [29] In previous reports on varicella-associated HSP, varicella occurred prior to or concomitantly with the onset of HSP. [30–34]…”
Section: Discussionmentioning
confidence: 99%